Aspects of green chemistry toward synthesis of benzazoles and quinoxalines: Bovine serum albumin-water system for C–N/C–S bond formation. Issue 6 (19th March 2022) - , Saima; Lavekar, Aditya G.; Equbal, Danish; Sinha, Arun K.
Abstract: In this report, a biocatalytic divergent approach of therapeutically important five-membered benzazole heterocyclic compounds such as benzothiazoles and benzimidazoles has been described wherein Bovine serum albumin (BSA) and water play cooperative role for oxidative cyclo-condensation reaction between 2-mercapto/amino anilines and aromatic aldehydes under air at room temperature. Further, this green strategy also extended for the synthesis of privileged and biologically important six membered quinoxalines, 2-phenylimidazo [1, 2-a]pyridine and benzo[d]imidazo[2, 1-b]thiazoles. Moreover, the present biocatalytic protocol for the synthesis of such five- and six-membered heterocyclic compounds also have the added benefits of high atom economy, operational simplicity, excellent yields, recyclability (up to four cycles), and gram scalability. Graphical abstract: UF0001